Diesel fuel filtration problems with modern common rail injection systems - Jocanović, Mitar T.; Karanović, Velibor V.; Knežević, Darko M.; Orošnjak, Marko D. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Modern diesel fuel injection systems called “common rail systems” have been increasingly developing over the past two years. Along with the development of such systems it has been, at the same time, necessary to follow the development of ancillary systems used for their proper and efficient operation. This paper provides a detailed presentation of the latest generation of common rail systems operating at high pressure together with problems regarding diesel fuel filtration.